Kidney transplantation with donors in severe acute kidney injury. Should we use these organs? Retrospective Case Series - Santos, Guilherme Palhares Aversa; Andrade, Luis Gustavo Modelli De; Valiatti, Mariana Farina; Contti, Mariana Moraes; Nga, Hong Si; Takase, Henrique Mochida (Sociedade Brasileira de Nefrologia, 2019)
ABSTRACTIntroduction: The number of incident and prevalent patients on dialysis has increased, as well as the number of candidates for renal transplantation in Brazil, without a proportional increase in the number of organ donors. The use of expanded kidneys, as to renal function, may be an alternative to increase the supply of organs.Objective: to discuss the feasibility of using expanded kidneys for renal function, which are in severe acute renal injury.Methods: All cases of renal transplantation of deceased donors performed at the Hospital das Clínicas de Botucatu of UNESP, from January 2010 to June 2018, totaling 732 cases were evaluated. Cases with final donor creatinine greater than 6 mg/dL were selected.Results: four patients were selected, of whom all donors were in severe acute kidney injury (AKI). These donors presented rhabdomyolysis as a probable cause of severe AKI, were young, with no comorbidities and had decreased urinary volume in the last 24 hours. The clinical evolution of all the recipients was satisfactory, with a glomerular filtration rate after transplantation ranging from 48 to 98 mL/min/1.73 m2.Conclusion: this series of cases shows the possibility of using renal donors in severe AKI, provided the following are respected: donor age, rhabdomyolysis as the cause of AKI, and implantation-favorable biopsy findings. Additional studies with better designs, larger numbers of patients and longer follow-up times are needed.

RESUMOIntrodução: O número de pacientes incidentes e prevalentes em diálise tem aumentado, assim como o número de candidatos ao transplante renal no Brasil, sem um aumento proporcional do número de doadores de órgãos. O uso de rins expandidos, quanto à função renal, pode ser uma alternativa para aumentar a oferta de órgãos.Objetivo: discutir a viabilidade do uso de rins expandidos quanto à função renal, que estejam em lesão renal aguda severa.Métodos: foram avaliados todos os casos de transplante renal de doador falecido realizados no Hospital das Clínicas de Botucatu da UNESP, de janeiro de 2010 a junho de 2018, totalizando 732 casos. Selecionou-se os casos com creatinina final do doador maior do que 6 mg/dL.Resultados: quatro pacientes foram selecionados, dos quais todos os doadores estavam em lesão renal aguda (LRA) severa. Esses doadores apresentavam rabdomiólise como provável causa de LRA severa, eram jovens, sem comorbidades e apresentavam diminuição de volume urinário nas últimas 24 horas. A evolução clínica de todos os receptores foi satisfatória, com taxa de filtração glomerular após o transplante variando entre 48 a 98 mL/min/1,73m2.Conclusão: essa série de casos mostra a possibilidade de utilização de doadores renais em LRA severa, desde que respeitadas as condições seguintes: idade do doador, rabdomiólise como causa de LRA e achados de biópsia favoráveis à implantação. Estudos adicionais com melhores desenhos, maior número de pacientes e maiores tempos de seguimento são necessários.
Transplante renal com doadores em lesão renal aguda severa. Devemos utilizar esses órgãos? Série de casos retrospectiva
Keywords: Kidney Transplantation; Tissue Donors; Delayed Graft Function; Acute Kidney Injury; Transplante de Rim; Doadores de Tecidos; Função Retardada do Enxerto; Lesão Renal Aguda